Pungent and volatile constituents of dried Australian ginger - Joel B. Johnson; Janice S. Mani; Simon White; Philip Brown; Mani Naiker (Current Research in Food Science, 2021)
Ginger is well known for its pungent flavour and health-benefitting properties, both of which are imparted by various gingerol derivatives and other volatile constituents. Although there has been a considerable amount of research into the chemical constituents found in fresh ginger, there is little information available on the quality of Australian-grown dried ginger, particularly that intended for processing purposes. Here, we investigate differences in the chemical composition of three samples of processing-grade ginger, ranging from very poor to good quality. Gingerols and 6-shogaol were quantified using high performance liquid chromatograph (HPLC), while gas chromatography coupled with mass spectrometry (GC-MS) was used to identify and semi-quantify the volatile constituents and other gingerol derivatives. Significant differences were found between the samples in their content of gingerols and [6]-shogaol, as well as in their total phenolic content and antioxidant capacity. A total of 100 volatile compounds were identified in the dried ginger samples, including 54 terpenoid derivatives and 35 gingerol derivatives. Several compounds are reported from ginger for the first time, including limonene glycol and neryl laurate. In addition, we provide the second report of the presence of shyobunol, geranyl-p-cymene and geranyl-α-terpinene in ginger.